PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS CANVA PADA MATA KULIAH PSIKOLOGI BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Manik Asta Jaya, Ketut; Yudista Witraguna, Kadek; Tri Wahyuni, Ni Nyoman (Jurnal Penjaminan Mutu, 2023)
This study aims to develop an interactive e-module in the learning process, especially to improve learning outcomes in the Learning Psychology course in the Elementary School Teacher Education Program (PGSD) at I Gusti Bagus Sugriwa Denpasar State Hindu University. This study is a Research and Development (R&D) study with the ADDIE stages. The results of this study indicate that the interactive e-module is feasible to be applied, as evidenced by the validation results from material experts stating that the interactive e-module is feasible with an average percentage of 77.5%. Validation by instructional design experts stated that the interactive e-module is included in the feasible category with an average percentage of 78%. Finally, validation by media experts stated that this learning media is in the feasible category with a percentage of 80%. Meanwhile, the trial results show that the interactive e-module is categorized as "practical" with a score of 3.17. From the pretest and posttest results, a significant improvement was obtained with an N-Gain score of 65%. The evaluation results from the use of this interactive e-module also serve as evidence of students' learning outcomes improvement